2013
DOI: 10.1111/odi.12086
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory properties of dental tissue‐derived mesenchymal stem cells

Abstract: In addition to their well-established self-renewal and multipotent differentiation properties, mesenchymal stem cells (MSCs) also possess potent immunomodulatory functions both in vitro and in vivo, which render them a potential novel immunotherapeutic tool for a variety of autoimmune and inflammation-related diseases. The major mechanisms may involve (1) the secretion of an array of soluble factors such as prostaglandin E2 (PGE2 ), indoleamine 2, 3-dioxygenase (IDO), transforming growth factor-β (TGF-β), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 110 publications
3
116
0
4
Order By: Relevance
“…11 The multipotent capacity and the immunomodulatory properties, both in vitro and in vivo of PDLSCs, retained these cells as a more accessible cell source than bone marrow-derived MSCs for cell-based therapy of immune and inflammation-related diseases. 36 In particular, the autologous periodontal ligament progenitors, mixed with bone-grafting material, when implanted into deep periodontal defects may be effective in regenerative dentistry. 37 Our previous studies provided evidence that the human periodontal ligament showed an accessible niche of stem cells which could differentiate into osteoblasts and adipocytes, secrete IL-7 and SDF-1a, 10,38,39 and express stemness markers such as nanog, Oct-4, SSEA-1, and SSEA-4.…”
Section: Discussionmentioning
confidence: 99%
“…11 The multipotent capacity and the immunomodulatory properties, both in vitro and in vivo of PDLSCs, retained these cells as a more accessible cell source than bone marrow-derived MSCs for cell-based therapy of immune and inflammation-related diseases. 36 In particular, the autologous periodontal ligament progenitors, mixed with bone-grafting material, when implanted into deep periodontal defects may be effective in regenerative dentistry. 37 Our previous studies provided evidence that the human periodontal ligament showed an accessible niche of stem cells which could differentiate into osteoblasts and adipocytes, secrete IL-7 and SDF-1a, 10,38,39 and express stemness markers such as nanog, Oct-4, SSEA-1, and SSEA-4.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies report that MSCs lack expression of MHC class II and most of the classical co-stimulatory molecules, such as CD80, CD86 and CD40 [47,48]. MSCs have been shown to regulate the activity in a range of effector cells involved in both innate and adaptive immunities.…”
Section: Therapeutic Potential Of Mscs In Gi Syndromementioning
confidence: 99%
“…Regarding the former, the potential mechanisms underlying this immunosuppression are the capacity of MSC to downmodulate immune reactions performed by T cells, B cells, dendritic cells (DC) and natural killer cells. However, regarding the latter, limited information is available on the effects of proinflammatory cytokines on MSC [Huang et al, 2009;Li et al, 2014].…”
Section: Immunomodulatory Properties Of Shedmentioning
confidence: 99%
“…In addition, the role of endogenous basic fibroblast growth factor in stem cells isolated from human exfoliated deciduous teeth might be the participation in colony formation and the ability of osteogenic differentiation [Miura et al, 2003;Li et al 2014;Sukarawan et al, 2014;Nowwarote et al, 2015].…”
Section: Properties Of Shedmentioning
confidence: 99%